Application of balanced scorecard in the evaluation of a complex health system intervention: 12 months post intervention findings from the BHOMA intervention: a cluster randomised trial in Zambia. - Wilbroad Mutale; Jeffrey Stringer; Namwinga Chintu; Roma Chilengi; Margaret Tembo Mwanamwenge; Nkatya Kasese; Dina Balabanova; Neil Spicer; James Lewis; Helen Ayles (PLoS ONE)
Introduction In many low income countries, the delivery of quality health services is hampered by health system-wide barriers which are often interlinked, however empirical evidence on how to assess the level and scope of these barriers is scarce. A balanced scorecard is a tool that allows for wider analysis of domains that are deemed important in achieving the overall vision of the health system. We present the quantitative results of the 12 months follow-up study applying the balanced scorecard approach in the BHOMA intervention with the aim of demonstrating the utility of the balanced scorecard in evaluating multiple building blocks in a trial setting. Methods The BHOMA is a cluster randomised trial that aims to strengthen the health system in three rural districts in Zambia. The intervention aims to improve clinical care quality by implementing practical tools that establish clear clinical care standards through intensive clinic implementations. This paper reports the findings of the follow-up health facility survey that was conducted after 12 months of intervention implementation. Comparisons were made between those facilities in the intervention and control sites. STATA version 12 was used for analysis. Results The study found significant mean differences between intervention(I) and control (C) sites in the following domains: Training domain (Mean I:C; 87.5.vs 61.1, mean difference 23.3, p = 0.031), adult clinical observation domain (mean I:C; 73.3 vs.58.0, mean difference 10.9, p = 0.02 ) and health information domain (mean I:C; 63.6 vs.56.1, mean difference 6.8, p = 0.01. There was no gender differences in adult service satisfaction. Governance and motivation scores did not differ between control and intervention sites. Conclusion This study demonstrates the utility of the balanced scorecard in assessing multiple elements of the health system. Using system wide approaches and triangulating data collection methods seems to be key to successful evaluation of such complex health intervention. Trial number ClinicalTrials.gov NCT01942278.